Synthesis of Dendritic Macromolecule with Butane Diamine as Core - Qu, Hongjie; Feng, Shide; Bi, Hongmei; Sun, Taifan; Gao, Jinling (Asian Journal of Chemistry, 2015)
A new 0.5 G dendritic macromolecule is synthesized with butane diamine and ethyl acrylate through Michael addition reaction while a 1 G dendritic macromolecule is synthesized by amidation reaction. The influences of the mole ratio of ester and amine, temperature and time on product are also studied and the optimum conditions are obtained. The products are characterized by IR, GC/MS elemental analyzer and 1H NMR, the relative data testify our expectation.